Combining Whole Genome Sequencing Data from Human and Non-Human Sources: Tackling Listeria monocytogenes Outbreaks - Ingrid H. M. Friesema; Charlotte C. Verbart; Menno van der Voort; Joost Stassen; Maren I. Lanzl; Coen van der Weijden; Ife A. Slegers-Fitz-James; Eelco Franz (Microorganisms, 2023)
Listeria monocytogenes (Lm) is ubiquitous in nature and known for its ability to contaminate foods during production processes. Near real-time monitoring of whole genome sequences from food and human isolates, complemented with epidemiological data, has been used in the Netherlands since 2019 to increase the speed and success rate of source finding in the case of (active) clusters. Nine clusters with 4 to 19 human cases investigated between January 2019 and May 2023 are described. Fish production sites were most often linked to outbreaks of listeriosis (six clusters), though other types of food businesses can face similar Lm problems, as the production processes and procedures determine risk. The results showed that low levels of Lm in food samples can still be linked to disease. Therefore, the investigation of a cluster of cases and deployment of the precautionary principle helps to focus on safe food and to prevent further cases. Good practice of environmental monitoring within a food business allows early detection of potential issues with food safety and helps food businesses to take appropriate measures such as cleaning to prevent regrowth of Lm and thus future outbreaks.